AVA Nexus e a Produção Discente em Rede na Graduação da ECA-USP: Da Informação ao Conhecimento - Passarelli, Brasilina; Vetritti, Fabiana Grieco Cabral de Mello (Revista de Graduação USP, 2017)
The conception and implementation of VLE NEXUS – from Information to Knowledge (http://nexus.futuro. usp.br) is based on the disciplines Information Resources I and II, devoted to the 4th and 5th semester students of the Librarianship and Documentation Undergraduate course at the School of Communications and Arts of the Universidade de São Paulo (ECA-USP). It was implemented in the 2000s, and at that time it was an avant-garde project, stimulating the hybrids face-to-face courses anchored in a VLE – Virtual Learning Environment and functioning as platform for publishing individual and collective activities of students and also as learning objects repository (LOR). This article aims to characterize the VLE, as well as to present indicators of individual and collective student production over thirteen years (2002-2015). With this work we hope to contribute to the debate about the importance of learning objects repository and of VLE in the construction of a new set of MIL – Media and Information Literacy among the undergraduate students of ECA-USP and, by extension, higher education institutions (HEIs) that use blended learning methodology in face-to-face courses.